On a new species of Isomeria Beck and redescription of species of Labyrinthus Beck from South America (Gastropoda: Stylommatophora: Camaenidae) - Cuezzo, Maria Gabriela (Zootaxa, 2006)
The Camaenid genera Labyrinthus Beck, 1837 and Isomeria Beck, 1837 are mainly distributed in northern South America. Current anatomical information available for both genera is scarce, particularly that concerning Isomeria species. The morphology of the pallial organs, genital and digestive systems of three species of Labyrinthus [L. subplanatus (Petit, 1843), L. dunkeri (Pfeiffer, 1852), L. tarapotoensis Moricand, 1858] and a new species of Isomeria are described. The morphology of hooked denticles that topped wall ridges inside penis and vagina in some species of Labyrinthus and in Isomeria are species-specific characters, differing in shape and size. These structures were not sufficiently studied either in Isomeria or in Labyrinthus and are absent in all anatomically studied species of  Solaropsis Beck, 1837, their sister genus. The presence of a bursa copulatrix sac reflexed over its duct is a character shared by all Labyrinthus species in which soft anatomy is known, and it was identified as a synapomorphy in a published phylogeny. Isomeria awa. n.sp. differs from other species of the genus mainly in shell morphology and characters of the distal genitalia. The presence of a stimulator-like structure in the vagina as well as the presence of a glandular pouch in the vagina are diagnostic characters of this new species, not present in the closely Camaenid related genera.